2018
DOI: 10.1111/aor.13364
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Machine Perfusion Versus Static Cold Storage in Deceased Donor Kidney Transplantation: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Static cold storage (SCS) and hypothermic machine perfusion (HMP) are two primary options for renal allograft preservation. Compared with SCS, HMP decreased the incidence of delayed graft function (DGF) and protected graft function. However, more evidence is still needed to prove the advantages of the HMP. In this study, the outcomes of kidney grafts from the two preservation methods were compared by conducting a systematic review and meta-analysis. Randomized controlled trials (RCTs) comparing the effect of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 34 publications
(134 reference statements)
2
49
0
11
Order By: Relevance
“…Our results, obtained in a model of severe IRI , suggest that an oxygen carrier such as M101 could be a valuable therapeutic option allowing to improve kidney protection during the hypothermic preservation window. While static CS is not recommended for injured kidneys , the present results support the notion that the use of M101 could improve function recovery, particularly in situations where no other option is available. On the other hand, the MP arm revealed that this technology, currently recommended for high‐risk organs , can be potentiated by M101.…”
Section: Discussionsupporting
confidence: 73%
“…Our results, obtained in a model of severe IRI , suggest that an oxygen carrier such as M101 could be a valuable therapeutic option allowing to improve kidney protection during the hypothermic preservation window. While static CS is not recommended for injured kidneys , the present results support the notion that the use of M101 could improve function recovery, particularly in situations where no other option is available. On the other hand, the MP arm revealed that this technology, currently recommended for high‐risk organs , can be potentiated by M101.…”
Section: Discussionsupporting
confidence: 73%
“…Panxin Peng et al of the Peking University China‐Japan Friendship School of Clinical Medicine, Beijing, China investigated as a systemic review and meta‐analysis hypothermic machine perfusion (HMP) versus static cold storage (SCS) in deceased donor kidney transplantation. Randomized controlled trials (RCTs) comparing the effect of hypothermic machine perfusion and static cold storage in deceased donor kidney transplantation were identified through searches of the MEDLINE, EMBASE, and Cochrane databases between January 1, 1980 and December 30, 2017.…”
Section: Transplantation and Organ Preservationmentioning
confidence: 99%
“…In deceased-donor kidney transplantation (KT), a prolonged cold ischemia time (CIT) has been identified as an independent risk factor for delayed graft function (DGF), acute rejection (AR), and poor graft survival [1,2]. It has been demonstrated that there is a proportional and independent increase in the risk of graft loss and patient mortality for each additional hour of CIT [2].…”
Section: Introductionmentioning
confidence: 99%
“…In deceased-donor kidney transplantation (KT), a prolonged cold ischemia time (CIT) has been identified as an independent risk factor for delayed graft function (DGF), acute rejection (AR), and poor graft survival [1,2]. It has been demonstrated that there is a proportional and independent increase in the risk of graft loss and patient mortality for each additional hour of CIT [2]. Furthermore, the extension of donor criteria to meet the transplant demand has led to the inclusion of high-risk categories such as donors after circulatory death (DCD) or donors with advanced age or significant comorbidities, which all show a higher susceptibility to ischemia-reperfusion injury [3].…”
Section: Introductionmentioning
confidence: 99%